Álgebras de explosão de certos ideais monomiais - Dantas, Ariane Pinto (2022)
In this dissertation we study the blowup algebras of monomial ideals over a polynomial ring in three variables. We deal with the hypotheses that the syzygy matrix of those ideals are of Hilbert-Burch type with linear entries and, moreover, these ideals have exactly 2 minimal primes. From these hypotheses, we proved that the syzygy matrix have a canonical format. Finally, we present a detailed discussion on blowup algebras for some well-structured canonic formats.